Collection, conservation and utilisation of indigenous ornamental crops - Gupta, Veena (Indian Horticulture, 2019)
Ornamental crops are the commodities of multi faceted enterprises in India, comprising traditional flower cultivation, indoor plants, loose flower production mainly for worship and dry flower decoration industry. These also include the ornamental foliage plants which contribute a lot towards the national income of various countries worldwide due to their striking appearances. India has a great diversity of these plants inhabiting varied agro-climatic zones from Leh- Ladakh to Rajasthan and from northeast to down south.